A Regulatory Signaling Loop Comprising the PGAM5 Phosphatase and CK2 Controls Receptor-Mediated Mitophagy - Chen, Guo; Han, Zhe; Feng, Du; Chen, Yanfang; Chen, Linbo; Wu, Hao; Huang, Li; Zhou, Changqian; Cai, Xiangyu; Fu, Changying; Duan, Liangwei; Wang, Xiaohui; et al. (Molecular cell, 2014)
Mitochondrial autophagy, or mitophagy, is a major mechanism involved in mitochondrial quality control via selectively removing damaged or unwanted mitochondria. Interactions between LC3 and mitophagy receptors such as FUNDC1, which harbors an LC3-interacting region (LIR), are essential for this selective process. However, how mitochondrial stresses are sensed to activate receptor-mediated mitophagy remains poorly defined. Here, we identify that the mitochondrially localized PGAM5 phosphatase interacts with and dephosphorylates FUNDC1 at serine 13 (Ser-13) upon hypoxia or carbonylcyanide p-trifluoromethoxyphenylhydrazone (FCCP) treatment. Dephosphorylation of FUNDC1 catalyzed by PGAM5 enhances its interaction with LC3, which is abrogated following knockdown of PGAM5 or the introduction of a cell-permeable unphosphorylated peptide encompassing the Ser-13 and LIR of FUNDC1. We further observed that CK2 phosphorylates FUNDC1 to reverse the effect of PGAM5 in mitophagy activation. Our results reveal a mechanistic signaling pathway linking mitochondria-damaging signals to the dephosphorylation of FUNDC1 by PGAM5, which ultimately induces mitophagy. [Display omitted] •FUNDC1 dephosphorylation at Ser-13 activates mitophagy•PGAM5 and CK2 regulate the reversible phosphorylation of FUNDC1•Knockdown of PGAM5 abrogates receptor-mediated mitophagy•CK2 and Src kinase functionally cooperate to regulate FUNDC1-mediated mitophagy Mitochondrial autophagy, or mitophagy, is a major mechanism involved in mitochondrial quality control. Chen et al. describe a regulatory signaling loop comprising the PGAM5 phosphatase and CK2 that controls receptor-mediated mitophagy.